2021
DOI: 10.1038/s41586-021-03676-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanobodies from camelid mice and llamas neutralize SARS-CoV-2 variants

Abstract: o , T he od or a Hatziioannou, Paul D. B ie ni as z , M ic hel C. Nussenzweig, Peter D. Kwong & Rafael CasellasThis is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
176
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(199 citation statements)
references
References 46 publications
6
176
0
Order By: Relevance
“…At least two recent studies reported that antibodies could be detected up to 11 months after infection and provided evidence that that these antibodies originated in memory B cells, not plasmablasts(Tong et al, 2021; Turner et al, 2021a). Generation of SARS-CoV-2 memory B cells(De Gasparo et al, 2021; Schoof et al, 2020; Xu et al, 2021) is likely necessary for long-term protection since that is the mechanism by which most anti-viral vaccines work(Iwasaki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At least two recent studies reported that antibodies could be detected up to 11 months after infection and provided evidence that that these antibodies originated in memory B cells, not plasmablasts(Tong et al, 2021; Turner et al, 2021a). Generation of SARS-CoV-2 memory B cells(De Gasparo et al, 2021; Schoof et al, 2020; Xu et al, 2021) is likely necessary for long-term protection since that is the mechanism by which most anti-viral vaccines work(Iwasaki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The ternary structure may also be considered as illustrative of the potential behavior of a bispecific construct linking two nanobodies. The bivalent or multivalent binding by antibody or nanobody would be expected to increase neutralization potential ( 19 , 45 , 46 , 47 ). Superposition of Sb14–RBD–Sb68 or Sb45–RBD–Sb68 on V HH -E–RBD–V HH -U indicates that Sb14, Sb45, and V HH -E represent class 1 and class 2 in recognizing the epitopic region but do so in somewhat different orientations ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, while conventional antibodies that comprise two disulphide-linked polypeptides, heavy and light chain, typically require mammalian cells for production, nanobodies can be manufactured using readily available microbial systems. The potency of nanobodies against SARS-CoV-2 7 infection has been demonstrated in cell-based assays [8][9][10][11][12][13][14][15][16] and most recently in animal studies 17,18 . Several strategies for engineering VHH into a multivalent species are known.…”
mentioning
confidence: 99%